İSTİSHÂB DELİLİNE HANEFÎLERİN YAKLAŞIMI - Sarıtepe, Erdoğan (Fırat University, 2014)
Geçmişte sabit olan bir hükmün aksini bildiren bir delil olmadıkça mevcut halde de geçerli olduğunu kabul etmek diye tanımlanan istishâb, mahiyeti, türleri, İslam hukukunun genel kaideleri ile ilişkisi ve delil değeri açısından usulcüler arasında tartışma konusu olmuştur. Usul eserleri incelendiğinde istishabın değişik bakış açılarına göre farklı sayılarda taksim edildiği ve farklı şekillerde isimlendirildiği görülmektedir. Mesela Hanefilerden Debûsî ve Serahsî istishâbın dört türünden bahsederken, Semerkandî üç tür istishâbdan bahsetmektedir. Biz bu çalışmada sadece Hanefîlerin istishâba bakış açılarını inceleyeceğiz

The istishab presumption that defined as “ to accept the stable judgment in the absence of other proofs of islamic law al-adillah al-shariyyah is dabated by scholars of methodology alusul from different aspect. For example; it’s character, it’s divisions and it’s connection with the other proofs. When we study source of methodology of İslamic law Usul al-Fıkh we see that it was examined with different perspective and under different titles. For example Dabûsî and Sarahsî from Hanaphies divided it four parts. On the other hand, in the Samarkand’s classification, it is three parts. In this article we will study Hanaphies approach to the presumption
Approach of Hanaphies to Proof of Presumption